2021
DOI: 10.1007/s00520-021-06097-w
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis of fatigue in colorectal cancer patients during chemotherapy

Abstract: Purpose The aim of this longitudinal study was to analyze trends in fatigue among colorectal cancer patients during chemotherapy and examine the predictors of multidimensional fatigue. Methods A mixed sample of colorectal cancer patients who were receiving chemotherapy (N = 200) was recruited in China. The patients completed the Cancer Fatigue Scale (CFS) at baseline (before chemotherapy) and after 3 and 6 months of chemotherapy. Repeated measures ANOVAs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
2
7
0
1
Order By: Relevance
“…Early implementation of evidence‐based fatigue management strategies and care options will benefit patients during and after cancer therapy [47–50]. Our findings, along with the existing evidence [8, 37, 51], are in accordance with guidelines from the National Comprehensive Cancer Network that call for initiating early screening for fatigue and continual monitoring of fatigue until treatment completion.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Early implementation of evidence‐based fatigue management strategies and care options will benefit patients during and after cancer therapy [47–50]. Our findings, along with the existing evidence [8, 37, 51], are in accordance with guidelines from the National Comprehensive Cancer Network that call for initiating early screening for fatigue and continual monitoring of fatigue until treatment completion.…”
Section: Discussionsupporting
confidence: 82%
“…Compared to other cancer-related symptoms such as pain and nausea, fatigue has a greater negative impact on daily activities and QoL [4][5][6]. Fatigue can persist for months or years following cancer diagnosis [7,8]; late-onset fatigue has also been documented among post-treatment cancer survivors [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, patients with poor QoL suffered from increased fatigue. Fatigue is the most commonly experienced side effect of cancer and cancer treatment ( 13 , 49 , 50 ). In addition, it is more common in older patients and among those with a lower socioeconomic status ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue is the most commonly experienced side effect of cancer and cancer treatment ( 13 , 49 , 50 ). In addition, it is more common in older patients and among those with a lower socioeconomic status ( 50 ). It has been demonstrated that increased levels of fatigue are not only associated with ongoing chemotherapy sessions but can also last for several years after the completion of chemotherapy ( 13 , 49 , 51 ).…”
Section: Discussionmentioning
confidence: 99%